Ceftriaxone attenuates Poly I:C–induced neuroinflammation in vitro by modulating glutamate transport, synaptic integrity, and immunometabolic reprogramming - Shi, Xizi; Sun, Yesheng; Hosseini, Shirin; Chen, Fangfang; Cordes, Thekla; Michaelsen-Preusse, Kristin; Korte, Martin (Frontiers in Cellular Neuroscience, 2025)
IntroductionNeuroinflammation triggered by viral infections is increasingly recognized as a driving force in neurodegenerative disease, promoting chronic neuronal injury and cognitive decline. A central mechanism in this process is impaired glutamate clearance due to downregulation of the astrocytic glutamate transporter GLT-1 (EAAT2/SLC1A2), which exacerbates excitotoxicity and neuronal death.MethodsIn this study, we assessed the neuroprotective effects of the β-lactam antibiotic ceftriaxone—a known upregulator of GLT-1—in an in vitro tri-culture model of neurons, microglia, and astrocytes challenged with the viral mimic polyinosinic:polycytidylic acid (Poly I:C).Results and discussionPoly I:C exposure elicited robust microglial and astrocytic activation and increased levels of TNF-α, IL-6, and IL-10. Concomitantly, we observed significant downregulation of GLT-1, synapse loss, impaired synaptic plasticity, and disrupted amino acid metabolism. A complementary Mendelian randomization analysis of GWAS data revealed that genetically determined alterations in plasma amino acid levels are significantly associated with the risk of five major neurodegenerative disorders, underscoring the role of metabolic dysregulation in disease pathogenesis. Treatment with ceftriaxone effectively reversed the Poly I:C–induced phenotypes: GLT-1 expression, dendritic spine density, and measures of synaptic plasticity were all restored, and abnormalities in amino acid and tricarboxylic acid cycle metabolites normalized. These findings highlight ceftriaxone’s multifaceted neuroprotective profile—modulating glutamate homeostasis, preserving synaptic integrity, and rebalancing metabolic pathways—and support its potential as a therapeutic agent to prevent neuronal degeneration in the context of virus-driven neuroinflammation.